Physiological responses during aerobic interval swimming training: effects of interval duration - Bentley, D. J.; Roels, B.; Libicz, S.; Hellard, P.; Millet, G. P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The aim of endurance training is to improve physiological variables such as maximal aerobic power (VO2max) and also performance. Aerobic interval training (IT) is known to induce improvements in these parameters (Gorostiaga et al., 1991). It has been suggested that the duration sustained at an intensity close to VO2max during IT maybe an important factor in longitudinal adaptation of VO2max (Billat et al., 2001). However, the nature of an IT session can be changed by modification of the duration, intensity and number of repetitions together with the rest interval between each work effort. The question of how work interval duration influences the duration sustained at or near VO2max during IT has been examined in cycling and running, but not in swimming where there is limited physiological data due to the technical difficulties of measuring oxygen uptake during exercise. The aim of the present study was to determine the time sustained near VO2max and maximum heart rate (HRmax) in two different interval swimming sessions comprising the same overall time and at the same work-intensity but with different work interval duration. Methods Eight national-level swimmers (Mean ± SD age 18 ± 2 yrs; body mass 66.9 ± 6.5 kg and swim VO2max 55.7 ± 5.8 ml·kg-1·min-1) agreed to participate in this study. Each subject attended three experimental sessions at a 50m indoor pool over a one week period as part of their prescribed training. The first test comprised a 5 x 200m step wise maximal incremental test to exhaustion to to determine the pulmonary ventilation threshold (VT), VO2max, the velocity (m·s-1) associated with VO2max (vVO2max) and Hrmax (b·min-1). The remaining two tests involved two different IT sessions comprising 4x400m (IT4x400) or 16x100m (IT16x100) at a velocity representing 25% of the difference between the VT and the vVO2max (.25%). During each test VO2 and HR where measured using portable telemetry (Cosmed, K4, B2, Rome, Italy) and a respiratory valve and snorkle system (Cosmed, Rome, Italy). The time (s) > 95% VO2max and > 90% HRmax was calculated for each IT training session respectively. Results The average vVO2max and HRmax during the 5 x 200 incremental test was 1.42 ± 0.06 and 187.7 ± 3.7. The overall velocity during the IT16x100m and IT4x400m was not significantly different (1.35 ± 0.05 vs 1.32 ± 0.06). The time sustained > 95% VO2max in the IT16x100 (t16x100) and IT4x400 (t4x400) was significantly correlated (r=0.91; p<0.005). However, the time > 95% VO2max was not significantly different in the IT16x100 and IT4x400 (Figure 1). The HR > 90% HRmax was not significantly different between the two IT sessions (807 ± 329 vs 740 ± 264 s). Discussion/Conclusion The results of this study demonstrate that the duration of the work interval in IT in swimming at an exercise intensity Ä25% does not seem to have the same affect than in running (Millet et al., 2003). However, there was considerable individual variation in the VO2 sustained near VO2max in each training session. Therefore, some individuals may reach a higher exercise intensity in one type of training but not the other. This factor deserves further research to establish the characteristics of those athletes that influence the physiological responses in IT of short or longer duration repetitions. Furthermore, the longitudinal adaptation to the long or short duration IT, and those individuals that respond to either form of IT also remains to be investigated.